Third millennium capitalism : convergence of economic, energy, and environmental forces - Rogers, Wyatt M. (Praeger, 2000)
Technological advances, government policies, energy supply, the environment and population are all issues that must be addressed by private enterprise in holistic, humanitarian ways. This text presents these issues as challenges and opportunities for global capitalism.